Mineral Carbonation Potential (MCP) of Mine Waste Material: Derivation of an MCP Parameter - Jacobs, Anthony; Hitch, Michael; Mosallanejad, Sara; Bhatelia, Tejas; Li, Jiajie; Farhang, Faezen (MDPI AG, 2023)
The heterogenous mineralogy of ultramafic deposits hosting mining operations makes it challenging to accurately determine the waste rock’s mineral carbonation potential (MCP). Additionally, the significantly higher carbonation capabilities of olivine than serpentine add to the difficulty. To address this issue, in this work, a new and unique tool called the MCP calculator was developed as a Microsoft ExcelTM spreadsheet to accurately determine the amount of anthropogenic CO2 that a given rock mass can sequester through mineral carbonation. The program estimates the modal mineral abundance of ultramafic rocks to aid in MCP estimation. This tool is designed to be cost-effective and tailored for use by the mining industry, utilising abundant lithogeochemical data to evaluate their deposit as a potential substrate for industrial mineral carbonation operations. The paper introduces the MCP calculator, outlines a framework for developing the MCP parameter, and presents an example of its application. The calculator is specific to the mineral assemblage investigated at the Turnagain ultramafic complex in northern British Columbia but can be adjusted to study comparable deposits. The paper acknowledges that using waste rock in a mineral carbonation operation requires economic and practical decisions beyond the scope of the research.